Fertilización con boro y análisis genéticos de los ensayos de teca (Tectona grandis L.f) de MLR Forestal, Siuna, RAAN, Nicaragua - Loría-Maroto, Jonnathan (Instituto Tecnológico de Costa Rica, 2017)
The aim of this study is to determine if fertilization with boron in the soil, has an effect on growth in diameter and height in teak tree at 13 months of age in plantations located at Siuna, RAAN, Nicaragua. Boron doses was applied at factorial design: 2 doses and a control, at two clonal test owned by the company, trees were planted at 3x3 m and 1,5x1,5 m each one. It was determined by a Kruskal Wallis non-parametric test, at 1,5x1,5 m place (high density), boron has a negative effect on growth trees because: confused effect with high competitions between trees, low natural abundance of boron at soils, and, boron on teak has a little/low-concentration element. At 3x3 m test, through ANOVA test, it was found an effect positive of boron’s doses: where 12 g/tree was better. While total height, doses of 6 g and 12 g/tree, promoted a significant superior growth in relation to the control. It is very important, to continue the measurements of both test, to determine the residual effect of boron application over time.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2016.
Keywords: Suelos; Silvicultura; Fertilización forestal; Ingeniería forestal